Glutamine Supplementation Enhances the Effects of a Low FODMAP Diet in Irritable Bowel Syndrome Management - Rastgoo, Samira; Ebrahimi-Daryani, Nasser; Agah, Shahram; Karimi, Sara; Taher, Mohammad; Rashidkhani, Bahram; Hejazi, Ehsan; Mohseni, Fatemeh; Ahmadzadeh, Mina; Sadeghi, Amir; Hekmatdoost, Azita (Frontiers in Nutrition, 2021)
Background & Aims: Although irritable bowel syndrome (IBS) is one of the most common gastrointestinal disorders presenting to gastroenterologists, therapeutic strategies have not yet well established. Accordingly, we conducted a randomized, double-blind, placebo controlled, clinical trial to evaluate the possible superiority adding glutamine supplement to low fermentable oligo- di- mono- saccharides and polyols (FODMAP) diet in patients with IBS. Methods: Eligible adults were randomized to receive low FODMAP diet either with glutamine (15 gram/day) or placebo for 6 weeks. The primary end point was a significant reduction in IBS Severity Scoring System (IBS-SSS). Secondary end points were changes in IBS symptoms and quality of life. Results: Fifty patients were enrolled in the study, while 22 participants completed the study protocol in each group. The glutamine group had significant changes in total IBS-severity score, dissatisfaction of bowel habit and interference with community function (58% reduction; P<0.001, 57% reduction; P <0.001, 51% reduction; P=.043, respectively). Improvement in IBS-severity score of more than 45% was observed in 22 of 25 participants (88%) in glutamine group, while it was only in 15 of 25 participants (60%) in control group (P=0.015). Conclusions: Our findings indicate the superiority of adding glutamine supplementation to low FODMAP diet in amelioration of IBS symptoms, while confirming the beneficial effects of low FODMAP diet in IBS management.